Obstetric Risk Factors in Primigravida Patients With Early Postpartum Hemorrhage - Nayab, .; Fayaz Bukhari, Naila Qurutulain; Rabia, .; Azra, .; Kainat, Syeda; Ain Zaman, Qurat Ul (Biological and Clinical Sciences Research Journal, 2025)
Early postpartum hemorrhage remains a major contributor to maternal morbidity, even among primigravida women. Identifying modifiable obstetric risk factors can support timely prevention and preparedness. Evidence on the distribution of common risk factors in primigravida patients with early PPH is needed in routine obstetric practice. Objective: To determine the frequency of obstetric risk factors among early post-partum hemorrhage primigravida patients. Methodology: This study included 318 primigravida patients diagnosed with early PPH. Patients with bleeding dyscrasias, referred from other centres, and those with thyroid disorders or diabetes mellitus were excluded. Patients were assessed for the risk factors for PPH, such as multiple pregnancy, pre-labour rupture of membranes (PROM), induction of labour, non-progressing labour, and post-term pregnancy. Data was analysed using SPSS 25. Results: The cohort in the present study had a mean age of 28.81 ± 6.69 years and a mean gestational age of 40.86 ± 2.17 weeks. Regarding risk factors, induction of labour was observed in 142 patients (44.7%). Post-term pregnancy in 112 cases (35.2%), PROM in 49 (15.4%) cases, multiple pregnancies in 21 (6.6%) cases, and non-progressing labour in 14 (4.4%) cases. Conclusion: Several risk factors of early PPH in primigravida women were identified in this study; the most frequent risk factors were induction of labor, followed by post-term pregnancy and prelabor rupture of membrane.